The effect of sensory motor training by perceptual sensory apparatus on development of some special physical and mechanical abilities for 100 m. racers under 20 years - Saeed Shukur , Sarmad; Sadiq Dhiab, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Impact Resistance training with and against the trajectory of the motor in some physical abilities and the BioA 100-meter, mechanical racing run for young people. That Training Jogging for different distances Melt -Rubber ropes According to direction and reversed movement With Obligations To the border of scientific of components Pregnancy Training represents to a training trend Aimed To Events Developments In The link between Starting and running, According to the specific mechanical requirements Have It Of Development of force Explosive and quick and their components which To give Border To the level Special speed for Stages Sprint run 100 m and amounts Efforts Required instantaneous powers. Noted Researcher In That Over there Repeat For exercises The speed was born A pattern Kinetic Have Running 100, Which A reason In That Be Progress of capacity Of special In stages Performance Limited And almost Be Non Concrete. So Came This The Study To put Some Solutions With the use Means Assistance Like ropes. The rubber By Facilitative and be my fault for a purpose Achieve Integration In of capacity of physical and mechanical performance. Set of Running 100 m For the youth, Under 20 years old, the researcher conducted physical tests (a test ran 10 m, 30 m and 60 m and a test of achievement), frequency and length of steps, and then applied your workouts with resistors, and carried out tests of the dimensional, and there was a clear improvement in the special physical abilities, mechanical variables and the completion of the jogging.